2018
DOI: 10.1021/acscatal.8b04106
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Reduction to Methanol Catalyzed by Mn(I) PNP Pincer Complexes under Mild Reaction Conditions

Abstract: Well-defined Mn­(I) hydrido carbonyl PNP pincer-type complexes were tested as efficient and selective nonprecious transition metal catalysts for the reduction of CO2 to MeOH in the presence of hydrosilanes. The choice of reaction temperature and type of silanes proved to be pivotal to achieve fast reactions and high selectivity to the methoxysilyl- vs silylformate derivatives in DMSO. The catalytic data are complemented by DFT calculations, highlighting a stepwise CO2 reduction mechanism centered on the Mn cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 62 publications
0
62
0
3
Order By: Relevance
“…This solvent was chosen as it was previously demonstrated that it can assist CO 2 activation, for example in hydrosilylation reactions. [42,44] Under these conditions and using this solvent, the reaction gave (OC(H)O)Bpin, identified by the 1 THF a small amount of CH 3 OBpin (5.0 %) formed after ca. 5 h of reaction, reaching a maximum 5.5 % yield after 24 h. In all cases, incomplete HBpin conversion, responsible for the low yields, was qualitatively assessed from the persistence of the characteristic signals at 27.3 ppm and 28.7 ppm in the corresponding final 11 B NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This solvent was chosen as it was previously demonstrated that it can assist CO 2 activation, for example in hydrosilylation reactions. [42,44] Under these conditions and using this solvent, the reaction gave (OC(H)O)Bpin, identified by the 1 THF a small amount of CH 3 OBpin (5.0 %) formed after ca. 5 h of reaction, reaching a maximum 5.5 % yield after 24 h. In all cases, incomplete HBpin conversion, responsible for the low yields, was qualitatively assessed from the persistence of the characteristic signals at 27.3 ppm and 28.7 ppm in the corresponding final 11 B NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, very mild conditions were applied (25 °C, 1 bar CO 2 ), in the presence of HBpin (0.224 mmol) and complex 1 (1.0 mol % with respect to HBpin), choosing [D 6 ]dmso as solvent. This solvent was chosen as it was previously demonstrated that it can assist CO 2 activation, for example in hydrosilylation reactions . Under these conditions and using this solvent, the reaction gave (OC(H)O)Bpin, identified by the 1 H NMR signal at 8.18 ppm and the 11 B NMR broad signal at 21.21 ppm, as the only C1‐product in ca.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gonsalvi et al. reported the first example of Mn I ‐catalyzed CO 2 hydrosilylation ( 21 ; Scheme ) . They demonstrated that selective reduction to silyl formate and silyl methoxide could be achieved by controlling either the limiting reagent (CO 2 vs. silane) or reaction temperatures (room temperature vs. 80 °C).…”
Section: Tm Catalysismentioning
confidence: 99%
“…While the hydrogenation of CO 2 can afford a variety of products and is a desirable process in terms of atom economy, the use of silane reductants allows for the use of significantly milder reaction conditions (T<100 °C, P CO2 <3 atm), and benefits thermodynamically from the stability of the generated products featuring Si−O bonds [7–9] . In addition, the use of silanes has allowed for the development of catalytic systems which exercise greater control over selectivity for products with different carbon oxidation levels, including silyl formates, silyl acetals, methoxysilanes and methane (which is formed in conjunction with bis(silyl)ethers) [8–13] …”
Section: Introductionmentioning
confidence: 99%